2015
DOI: 10.2172/1225310
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Views on Transportation and Advanced Vehicle Technologies

Abstract: who provided helpful insights into how vehicle technologies might be accepted into the marketplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A recent survey found that only 24% of respondents were even considering purchasing a small sedan. 501 Some 68% of respondents indicated that they would consider paying a premium for an EV, but an HEV with a $2,000 premium was preferred to a PHEV with a $4,000 premium. Half of the respondents said that availability of wireless charging would increase their willingness to consider a BEV.…”
Section: Markets and Market Actors Light-duty Consumersmentioning
confidence: 99%
“…A recent survey found that only 24% of respondents were even considering purchasing a small sedan. 501 Some 68% of respondents indicated that they would consider paying a premium for an EV, but an HEV with a $2,000 premium was preferred to a PHEV with a $4,000 premium. Half of the respondents said that availability of wireless charging would increase their willingness to consider a BEV.…”
Section: Markets and Market Actors Light-duty Consumersmentioning
confidence: 99%
“…NAS (2015) reports on a Pike Research (2012) study that found that 55% of vehicle shoppers had "favorable" or "very favorable" impressions of PEVs (a decline from 62% in 2009), despite much lower purchase rates. Singer (2015) also finds that a relatively high percentage of consumers (52%) said that PHEVs were "'just as good or better than' traditional ICEs," with a similarly high percentage (45%) saying the same for BEVs. Singer (2015) also finds that 48% of survey respondents can name a specific PEV make and model and 49% report having seen PEVs in parking lots (see Table 3 -3).…”
Section: Internal Searchmentioning
confidence: 91%
“…Singer (2015) also finds that a relatively high percentage of consumers (52%) said that PHEVs were "'just as good or better than' traditional ICEs," with a similarly high percentage (45%) saying the same for BEVs. Singer (2015) also finds that 48% of survey respondents can name a specific PEV make and model and 49% report having seen PEVs in parking lots (see Table 3 -3). However, more than 40% of respondents believed they had never been in or near a PEV and very few (18%) were aware of charging stations on their regular driving routes.…”
Section: Internal Searchmentioning
confidence: 91%
“…A series of long-standing surveys by J.D. Power and Opinion Research Corportation has asked consumers for their views on different vehicle attributes, including dependability, price, and fuel economy (Singer, 2015). People's opinion on the most important attribute is strongly correlated with the price of fuel, as shown in Figure 21 (DOE, 2016a).…”
Section: Miscellenaeous Trends In the Fact Of The Weekmentioning
confidence: 99%